Iron-sulfur clusters in SARS-CoV-2 exoribonuclease and methyltransferase complexes: relevance for viral genome proofreading and capping - Nunziata Maio; Umberto Terranova; Yan Li; J. Martin Bollinger Jr.; Carsten Krebs; Tracey A. Rouault (Nature Communications)
Abstract Coronaviruses rely on a multifunctional replication-transcription complex to ensure genome fidelity and support viral propagation. Within this complex, the nsp14-nsp10 heterodimer possesses 3’−5’ exoribonuclease (ExoN) activity, while nsp14 alone functions as an N7-methyltransferase and the nsp16/nsp10 complex completes viral RNA capping via its 2′-O-methyltransferase. Here, we report that nsp14 and nsp10 ligate [Fe4S4] clusters when purified anoxically, in sites previously modeled as zinc centers. Quantum mechanics/molecular mechanics simulations revealed distinct reduction potentials for these iron-sulfur (Fe-S) clusters, and redox titrations demonstrated that changes in oxidation state modulate RNA binding by nsp14 and the nsp10/nsp16 complex. Functionally, Fe-S clusters enhance the methyltransferase activities of nsp14 and nsp10/nsp16, while leaving the ExoN activity unaffected. These findings uncover a redox-regulated role for Fe-S clusters in SARS-CoV-2 RNA processing and suggest that the viral core enzymatic functions may be modulated by the redox state of their Fe-S cofactors.